2002
DOI: 10.1023/a:1014842303583
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: (2S,1'S,2'R)-2-(Carboxycyclopropyl)glycine (L-CCG III) was a substrate of Na(+)-dependent glutamate transporters (GluT) in Xenopus laevis oocytes (IC50 to approximately 13 and to approximately 2 microM for, respec tively, EAAT 1 and EAAT 2) and caused an apparent inhibition of [3H]L-glutamate uptake in "mini-slices" of guinea pig cerebral cortex (IC50 to approximately 12 microM). In slices (350 microM) of guinea pig cerebral cortex, 5 microM L-CCG III increased both the flux of label through pyruvate carboxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Such movements may occur in response to changes in the activity of glutamatergic synapses and, therefore, activity of L-glu transport could be of importance not only for the normal operation of the synaptic excitation [5] but also as an indicator of local excitatory activity that would have to be matched by local changes in the metabolism and blood flow. Indeed, it has recently been demonstrated that not only pharmacological manipulation of glutamate receptors but, in particular, interference with GluT, can elicit specific metabolic responses in brain tissue [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Such movements may occur in response to changes in the activity of glutamatergic synapses and, therefore, activity of L-glu transport could be of importance not only for the normal operation of the synaptic excitation [5] but also as an indicator of local excitatory activity that would have to be matched by local changes in the metabolism and blood flow. Indeed, it has recently been demonstrated that not only pharmacological manipulation of glutamate receptors but, in particular, interference with GluT, can elicit specific metabolic responses in brain tissue [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…)-dependent ATPase in brain tissue [13]. Such a relationship could be important for the regulation of energy supply in response to changes in excitatory (glutamatergic) synaptic activity [14,15] and for the activity of metabolic pathways that are linked to glutamatergic neurotransmission and/or to functioning glutamate transport [16][17][18]. Testing the effect of rottlerin on the activity of the (Na ?…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this set includes the l-glutamate [42] (1) and both enantiomers of aspartate [43] (2, 3) as natural substrates. As substrate inhibitors the set includes: 4-methylglutamate isomers (4)(5), [42] l-threo-b-hydroxyaspartate (THA, 6), [6] l-threo-4-hydroxyglutamate (7), [42] l-sulphate-O-serine (l-SOS, 8), [9] three cyclopropyl derivatives (namely, l-CCG-III, 9, d-CCG-I, 10, and l-CCG-IV, 11), [44] four pyrrolidine dicarboxylates (namely, t-2,4 PDC, 12, 2,4MPDC, 13, l-3,4MPDC, 14, 4-Methyl-2,4 PDC, 15), [42] and cis-aminocyclobutyl dicarboxylate (cis-ABCD, 16). [9] Figure 2 includes the nontransported blockers which can be divided in three main groups: b-hydroxyaspartate derivatives (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), [45,46] aspartic acid amides (27)(28)(29)(30), [47] and diaminopropionic acid analogues (DAPAs, 31-32).…”
Section: Ligand Datasetsmentioning
confidence: 99%